Pathotype Determination of Xanthomonas oryzae pv. oryzae (Xoo), the causal agent of Bacterial Leaf Blight and Resistance Reactions of several Rice Varieties in South Sulawesi - Nurmujahidin, Nurmujahidin; Patandjengi, Baharuddin; Kuswinanti, Tutik; Darmawan, Andi Alfian (Departemen Hama dan Penyakit Tumbuhan Fakultas Pertanian Universitas Padjadjaran, 2025)
Bacterial leaf blight (BLB), caused by Xanthomonas oryzae pv. oryzae (Xoo), is a major disease of rice. This study aimed to determine the Xoo pathotypes present in rice-growing areas of South Sulawesi and to evaluate the resistance of selected rice varieties. The research was conducted at the Agricultural Biotechnology Research and Development Center and the Plant Pests and Diseases Laboratory, Hasanuddin University, Makassar. Xoo isolates were cultured on Wakimoto medium and inoculated using the clipping method. Five differential varieties (Kinmaze, Wase Aikoku, Tetep, Java 14, and Kogyoku) were used to classify the pathotypes, while five commercial rice varieties (Inpari 6, Ciliwung, Ciherang, IR 64, and Pioneer) were tested for resistance. Six Xoo isolates were classified into pathotypes VI, VII, VIII, and XI, with pathotype VIII being the most dominant (33.3%). Inpari 6 and Ciliwung showed resistance to all tested pathotypes. Ciherang was resistant to most pathotypes but moderately susceptible to VIII. IR 64 and Pioneer displayed varying degrees of resistance and moderate resistance. These findings highlight the presence of diverse Xoo pathotypes and identify rice varieties with broad-spectrum resistance, providing valuable information for the development of BLB management strategies suited to specific regional conditions.